PATH DEPENDENCE REPETITION DINAMIKA PERKEMBANGAN PARTAI PROTO ISLAM INDONESIA, SAREKAT ISLAM (1911-1940) - Agus Riyanto (LP2M, 2020)
This article aims to describe the trajectory of the development of Sarekat Islam (SI) in the pre-independence era by using path dependence analysis and critical junctures. In this context, important political decisions made by the proto-Islamic party agents will identify various alternatives determined by their antecedent conditions, as well as a series of follow-up causal events after critical junctures as path dependence patterns that lead to an outcome or outcome of the development of the SI organization. explained that there were three stages of the development of the Sarekat Islam organization, which transformed into the Sarekat Islam Party (PSI) and the Indonesian Sarekat Islam Party (PSII) which were produced by three agent decisions in moments of critical juntures, namely the stages of growth, division and decline. Key word : Critical junctures, Path dependence, the proto- Islamic